Dental treatment in diabetic patients: A narrative review (Research, Society and Development, 2023)
This narrative review of the literature aimed to evaluate dental treatment in diabetic patients. The articles were published in the last 10 years and the bibliographic survey was carried out through the CAPES Periodicals, PubMed, LILACS and Scielo databases, in English, Portuguese and Spanish, with exclusion and inclusion criteria. Through the results, it is possible to note that 3 to 4% of patients undergoing dental treatment are diabetic, frequently presenting oral manifestations such as periodontal disease, halitosis, salivary dysfunction, bacterial and fungal infections. The dental surgeon (DC) must have knowledge about the disease to identify and refer it to a doctor when necessary. It is essential to carry out a detailed anamnesis, with consultations always being short in the morning, 90 minutes after the first meal. Capillary blood glucose should also be checked with a glucometer before, during and after the consultation. It is concluded that dental treatment in individuals with diabetes must be carried out individually, following a convenient clinical approach. Since, visits to the DC must occur frequently, especially in situations of decompensation, which causes complications in both oral and systemic health. Therefore, it is essential for the patient to be integrated into a multidisciplinary team to carry out adequate treatment, always aiming for health and well-being.